Room‐Temperature Tunneling Behavior of Boron Nitride Nanotubes Functionalized with Gold Quantum Dots. (18th June 2013) - Lee, Chee Huei; Qin, Shengyong; Savaikar, Madhusudan A.; Wang, Jiesheng; Hao, Boyi; Zhang, Dongyan; Banyai, Douglas; Jaszczak, John A.; Clark, Kendal W.; Idrobo, Juan‐Carlos; Li, An‐Ping; Yap, Yoke Khin
<x xml:space="preserve">Abstract</x> One‐dimensional arrays of gold quantum dots (QDs) on insulating boron nitride nanotubes (BNNTs) can form conduction channels of tunneling field‐effect transistors. We demonstrate that tunneling currents can be modulated at room temperature by tuning the lengths of QD‐BNNTs and the gate potentials. Our discovery will inspire the creative use of nanostructured metals and insulators for future electronic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>